Thermally Induced Reversible Coagulation in Ceramic Powder-Polymer Liquid Suspensions - Horn, Jeffrey A.; Patterson, Burton R. (Journal of the American Ceramic Society, 1997)
It was observed that slurries of oxide powders in oxidized polybutene fluids can be caused to change reversibly between fluid, nearly Newtonian behavior and plastic behavior by modest changes in temperature. This phenomenon was believed to result from changes in the dispersion vs association among the particles. The rheological effects of temperature, polymer oxidation, and particle size were observed for 30 vol% slurries of TiO2, Al2O3, and ZrO2 powders in polybutene fluids. Elasticity (in oscillation) and low‐shear‐rate viscosity (in steady shear) were observed to increase with increasing temperature for TiO2 and Al2O3 particles in oxidized polybutene fluids. This behavior was attributed to the creation of interparticle structures. The attainment of this structure on heating was observed to be inhibited by increased oxidation of the polymer and increased particle size. It was concluded that the adsorption of oxidized molecules from the polymer liquid, along with the high viscosity of the bulk polymer, resulted in suspensions that were metastable against coagulation. Increased temperature resulted in lower viscosities of the liquid, allowing coagulation on a short time scale. The presence of the adsorbed polymer, however, prevented intimate contact among the particles so that the coagulated structure was easily destroyed upon subsequent cooling and shearing.